2017
DOI: 10.1007/s11696-017-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Power consumption for an agitated vessel equipped with pitched blade turbine and short baffles

Abstract: Power characteristics for an agitated vessel equipped with planar short baffles of length L and pitched blade turbine of pitch β are presented in the paper. The studies were carried out in the vessel of inner diameter D = 0.6 m, where the baffles were located in the distance p from the vessel bottom (p + L = H). Torque was measured using strain gauge method within the turbulent regime of the flow of Newtonian liquid in the agitated vessel. The effects of the pitch β and geometrical parameter p/H on the power n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…Results based on Rushton and flat paddles, which are typical radical impellers, were also reported by Major‐Godlewska and Karcz . Using the same vertical tubular coil, Major‐Godlewska and Karcz further investigated the power consumption, gas holdup, and residence time of gas bubbles in a gas‐solid‐liquid system.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Results based on Rushton and flat paddles, which are typical radical impellers, were also reported by Major‐Godlewska and Karcz . Using the same vertical tubular coil, Major‐Godlewska and Karcz further investigated the power consumption, gas holdup, and residence time of gas bubbles in a gas‐solid‐liquid system.…”
Section: Introductionmentioning
confidence: 63%
“…The gas holdup and power consumption characteristics of an agitated vessel equipped with a tubular vertical coil and an A315 axial impeller were reported by Major‐Godlewska and Karcz . Results based on Rushton and flat paddles, which are typical radical impellers, were also reported by Major‐Godlewska and Karcz . Using the same vertical tubular coil, Major‐Godlewska and Karcz further investigated the power consumption, gas holdup, and residence time of gas bubbles in a gas‐solid‐liquid system.…”
Section: Introductionmentioning
confidence: 84%
“…The authors concluded that the curvature of the blades had the most significant impact on power reduction and the efficiency of the mixing process. The energy consumption for an agitated vessel equipped with a pitched blade turbine and the performance impellers was the object of a detailed study in [8,9]. Due to their high-efficiency, the most high-speed turbine-type impellers are often used in industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been achieved on the effect of baffle design, including those of Bittins and Zehner [14], Karcz and Major [15], Ammar et al [16] and Kamla et al [17] for different impellers [a propeller, a pitched blade turbine (PBT) and a Rushton turbine (RT)]. The influence of some geometrical parameters of baffles (length, width, number and the clearance between the tank bottom and the lower edge of baffles) has been the subject of some studies [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%